Pembuatan Perangkat Elektroplating untuk Praktik di SMK Muhammadiyah 1 Moyudan Sleman - Arianto Leman Soemowidagdo; Arianto Leman Soemowidagdo (Jurnal Pengabdian Vokasi, 2025)
[The Electroplating Devices Manufakturing for Practice at SMK Muhammadiyah 1 Moyudan Sleman] SMK Muhammadiyah 1 Moyudan which located on Jl. Klangon-Tempel Km 4.5 Gedongan, Sumberagung, Moyudan, Sleman, DIY have Motorcycle Engineering and Business and Light Vehicle Engineering programs. In both programs, electroplating practice has not been electroplating practice has not been held since the absence of devices. The Mechanical Engineering Education Department service team of Yogyakarta State University which have expertise in developing equipment for practice, took the initiative to make a device for electroplating practice. The Four-D method was applied to create an electroplating practice device. The PAR method was applied to train teachers and education staff to perform the electroplating process. The electroplating devices equipped with 6 vessels so that able to accommodate the processes of hot degreasing, pickling, nickel strike and shiny nickel plating, and rinsing. The device is also equipped with a digital rectifier, temperature-controlled heater, aerator, and nickel anode in a titanium basket. Teachers and education staff have understood the theory of electroplating and are able to perform nickel plating with electroplating methods. However, learning modules are needed to improve the usefulness of electroplating practice devices.